A COMPARATIVE STUDY OF SOME VIRULENCE FACTORS AND PHYLOGENETIC CHARACTRIZATION OF Escherichia.coli ISOLATES CAUSING URINARY TRACT INFECTION AND THE COMMENSAL GUT MICROBIOTA - & et al., Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Variety of virulence factors are involved in the pathogenicity of Escherichia coli isolates, the common cause of the urinary tract infections.(UTIs). This study was aimed.to determine some virulence factors.involved in the pathogenicity.and the phylogenetic.grouping of uropathogenic E. coli isolates.from UTIs in compare.with isolates.from gut.microbiota (fecal flora) In.this study ,E coli isolates  were collected from  samples .urine (n = 25), fecal samples (n = 25) samples of  the same patients with UTI, and from fecal samples (n= 5 as control )of patients without UTI. The detection of phylogenetic grouping and some virulence genes among the all isolates were confirmed by PCR technique. The results.showed that.phylogenetic groups B2,B1(36%) and D (28%) were predominated.among uropathogenic E.coli  in comparison with group A (8%) ,whereas in .commensal isolates.groups B1(36%), B2(32%) ,D (28%) were.more prevalent in compare.with group A (4%).The prevalence.of cnf1 and fimH .genes were higher in.UPEC in comparsion with.commensal isolates. However, the.prevalence of kpsMT II gene.was similar among.both groups, while hlyA gene was.higher in fecal.isolates. According to this results., microbiota may considered the main source of UPEC bacteria.